Parking lot availability database for pattern mining - Yap, Hui Fung (2014)
As of 2013, the car ownership rate in Singapore is roughly about 12 cars for every 100 people, which makes up to 600 thousands car being owned in Singapore. Every single car has to be parked somewhere at any time when it is not moving. In a small country like Singapore, the need to efficiently manage parking availability becomes a tricky problem to handle. Failure to do so may result in heavy congestion or even accidents within the parking facilities.[1]